INTEGRASI KAWASAN PARIWISATA KOTAWARINGIN BARAT, SUKAMARA, DAN LAMANDAU (KOBARSULAM) MELALUI PENGEMBANGAN JALUR WISATA TEMATIK - Raksapati, Abadi; Dahlan, Mohammad Zaini; Endy, Endy (Pusat Perencanaan dan Pengembangan Kepariwisataan, 2025)
Tourism development in the West Kotawaringin, Sukamara and Lamandau (Known as Kobarsulam Region) is currently not yet integrated and mutually supportive. West Kotawaringin as a tourist entrance and the region's main tourism destination has not been able to spread tourist visits and tourism benefits to surrounding areas. Efforts to integrate tourism development in Kobarsulam must involve all existing tourism stakeholders. One of the strategies that can be encouraged in building tourism integration in Kobarsulam is by developing tourist trails that link the themes and stories of various tourist attractions throughout the region. Based on the study, there are at least nine thematic tourism trails that can be developed, namely the thematic tourism trails Visiting The Borneo Orang Utan House, Exploring The Borneo River, Historical Traces of The Kutaringin Sultanate, Dayak Cultural Exoticism, Exploring the Civilization of the South Coast of Kalimantan, Tourism Events, Exploring the Tropical Forest of Kalimantan, Water Recreation, and Authentic Kobarsulam Culinary.